Ecology of insect on beneficial plant in oil palm plantation: a review / Junaina Sarip - Sarip, Junaina (Faculty of Plantation and Agrotechnology, 2017)
This review primarily focusing on evaluate the ecology of insect on beneficial plant in oil palm plantation. The objectives of this review are to evaluate the population of insect on beneficial plant, to evaluate the factor affecting the population of insect on beneficial plant and lastly to evaluate the beneficial plant that can provide better survival resources. Beneficial plant, Antigonon leptopus and Turnera subulata are introduced in order to control the insect population in oil palm plantation. Order of Diptera, Lepidoptera, Coleoptera, Orthoptera, Isoptera and Hymenoptera was collected using the Malaise trap. Where, from the finding Turnera subulata was better to attract insect from order Hymenoptera (59%) than Antigonon leptopus only attract (39%) of Hymenoptera. Hymenoptera was an order that can regulated the insect population especially Metisa plana, where it can regulated up to 36.7% of Metisa plana population.